Fungal resistance of particleboard made using glutardialdehyde modified corn starch as the binder with the aid of urea formaldehyde resin - Mohamad Amini, Mohd Hazim; Hashim, Rokiah; Sulaiman, Nurul Syuhada; Sulaiman, Othman; Abu Bakar, Mohamad Bashree; Mohamed, Mazlan; Rahman, Rozyanty (Science Publishing Corporation Inc., 2018)
Particleboard is a popular wood composite made using mixtures of wood particles and resin, binder or adhesives, pressed at high temperature to cured. Despite its popularity, formaldehyde-based adhesives used in the formulations lead to cancerous effect as the formaldehyde fumes released from the unreacted chemicals travel into human lungs. Therefore this study tries to reduce the utilization of formaldehydebased resin by replacement of a significant portion of the binder with glutardialdehyde modified corn starch as the binder. However, this practice could lower the durability of the particleboards against biological attack. Therefore, this study evaluates the fungal resistance of the particleboard panels. Panels were manufactured using 83:15:2 ratio of wood, corn starch-modified with glutardialdehyde and formaldehyde resin, respectively, as an improvement. Four types of wood-degrading fungal were chosen including Trametes versicolor, Formitopsis palustris, Schizophyllum commune and Pycnoporus sangineus. Some of the particleboard showed a little increased in fungal resistance when 2% urea formaldehyde was added, compared to using glutardialdehyde modified corn starch and starch only as the binder. Nine out of twelve samples showed a decrement in fungal degradation by using glutardialdehyde modified starch as the binder. Meanwhile, 6 out of 12 samples showed higher fungal resistance after additional of 2% urea formaldehyde in the binder formulation. Based on the results, combination of modified corn starch and urea formaldehyde resin could have a potential to be used in particleboard making without reducing the initial resistance towards fungal attack.